2019
DOI: 10.1038/s41598-019-48632-0
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid induced a negative geotropic response in dark-incubated Chlamydomonas reinhardtii

Abstract: The phytohormone abscisic acid (ABA) plays a role in stresses that alter plant water status and may also regulate root gravitropism and hydrotropism. ABA also exists in the aquatic algal progenitors of land plants, but other than its involvement in stress responses, its physiological role in these microorganisms remains elusive. We show that exogenous ABA significantly altered the HCO 3 − uptake of Chamydomonas reinhardtii in a light-intensity-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Previous reports showed that heat treated Arabidopsis and rice leaves had increased ABA contents and exogenous ABA application improved heat tolerance in WT rice plants 43 , 44 . ABA is reported to be involved in tolerance to oxidative stress 45 , HCO3 − uptake 46 , and stress acclimation in Chlamydomonas 47 . TM6 displays similar expression patterns in both 35°C and 40°C treatments, with increased expression during early heat and reduced expression during early recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports showed that heat treated Arabidopsis and rice leaves had increased ABA contents and exogenous ABA application improved heat tolerance in WT rice plants 43 , 44 . ABA is reported to be involved in tolerance to oxidative stress 45 , HCO3 − uptake 46 , and stress acclimation in Chlamydomonas 47 . TM6 displays similar expression patterns in both 35°C and 40°C treatments, with increased expression during early heat and reduced expression during early recovery.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that heat treated Arabidopsis and rice leaves had increased ABA contents and exogenous ABA application improved heat tolerance in WT rice plants (Balfagón et al, 2019, 1;Li et al, 2020a). ABA is reported to be involved in tolerance to oxidative stress (Yoshida et al, 2003), HCO3 − uptake (Al-Hijab et al, 2019), and stress acclimation in Chlamydomonas (Colina et al, 2019) After 2-4 h recovery from 40°C, cells started to replicate DNA between 2-and 4-h of recovery at 25 o C, resulting in reduced 1C but increased 2C and 4C cell populations (Figure 4Q). DNA replication continued until 8-h of recovery, resulting in the accumulation of high-ploidy level cells, ranging from 1C to 16C (Figure 4S).…”
Section: Most Genes With Known Roles In Heat Response Belong To Transcriptomic Module 1 (Tm1)mentioning
confidence: 99%
“…It has been reported that heat treated Arabidopsis and rice leaves had increased ABA contents and exogenous ABA application improved heat tolerance in WT rice plants (Balfagón et al, 2019, 1;Li et al, 2020a). ABA is reported to be involved in tolerance to oxidative stress (Yoshida et al, 2003), HCO3 − uptake (Al-Hijab et al, 2019), and stress acclimation in Chlamydomonas (Colina et al, 2019). TM6 displays similar expression patterns in both 35 o C and 40 o C treatments, with increased expression during early heat and reduced expression during early recovery.…”
Section: Network Modeling Of Transcriptome and Proteome Revealed Expression Patterns Of Key Pathways During And After Heat Treatmentsmentioning
confidence: 99%
“…However, our knowledge about the biological function, biosynthesis, and possible signaling pathways in lower photosynthetic and non-photosynthetic organisms is quite limited. In lower photosynthetic organisms, several studies connect ABA to abiotic stress [48,50]. It was also shown that exogenous ABA modulates Chamydomonas reinhardtii HCO3 − uptake and that ABA concentration determines the position of this aquatic algae in the water column depending on light intensities, which could be one of the original functions of this hormone in regulating tropisms [50].…”
Section: Occurrence and Evolution Of Abamentioning
confidence: 99%